Deliberate self-harm among younger and older adults. Issue 7 (8th August 2016) - Segal, Daniel L.; Connella, Alyssa; Miller, Tory; Coolidge, Frederick L.
ABSTRACT: This study examined self-harming behaviors among younger and older adults who completed the Self-Harm Inventory (SHI). A 2 (age group) × 2 (gender) analysis of variance showed a significant main effect for age such that younger adult students ( M  = 3.42, SD  = 3.86) had higher SHI total scores than community-dwelling older adults ( M  = 1.58, SD  = 2.35). Younger adults endorsed "Yes" responses significantly more frequently than older adults on 13 of 22 items. Future research should examine specific behaviors of older adults who self-harm more frequently and explore relationships between self-harming behaviors and other risk and resiliency factors for elder suicide.